The Impact of Mass Media News, Social Media Content, Consumer Complaints, Risk-Based Capital, and Claim Expense Ratio on Premium Revenue of Unit-Linked Products in Indonesian Life Insurance Companies - Ardiansyah, Dody; Chabachib, Mochammad (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to analyze the impact of mass media coverage, social media content, consumer complaints, Risk Based Capital (RBC), and the ratio of claim expenses to life insurance premium income in Indonesia. The findings show that mass media coverage has no significant effect, while social media content with negative sentiment has a significant negative impact on premium income. Consumer complaints have no effect, but RBC has a positive effect and the claims expense ratio has a negative effect on revenue. In conclusion, even though mass media coverage is not significant, social media content has a big impact. High RBC levels and efficient claims management are important to maintain the stability of an insurance company's financial performance. Practical implications, insurance companies must strengthen communication strategies, especially on social media, as well as improve risk and claims management to maintain stable financial performance.